“A Person Taking Care of the Sick is also a Sick Person”: Challenges and Consequences of Hospital-Based Informal Caregiving - Kudus Oluwatoyin Adebayo PhD; Oluwaseyi Dolapo Somefun PhD; Mofeyisara Omobowale PhD; Marisa Casale PhD; Rukayat Usman MA; Atinuke Olujimi MSc; Funmilayo Omodara MPH (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Informal caregivers support relatives in healthcare facilities globally. However, their involvement in hospitalization care while residing in and around the hospital is more prevalent in under-resourced settings. This article examined the challenges and multifaceted consequences of hospital-based informal caregiving in a Nigerian tertiary health facility. The study adopted a non-experimental exploratory research design and ethnographic and qualitative techniques were used to collect data from 75 participants, comprising 21 informal caregivers, 15 inpatients, 36 hospital staff, and 3 ad-hoc/paid caregivers. The challenges identified include: physical health effects and infection risks; livelihood and economic impact; mental health effects; inadequate access to basic services; exposure to safety risks and violence; conflict and barriers within the health system; and social impact. These challenges have negative consequences on informal caregivers, including heightening their vulnerability to poor health and burdening them economically and socially. Informal caregivers play a crucial role in under-resourced settings. Policymakers should create a supportive healthcare environment that meets their needs, ultimately improving the overall quality of care provided in tertiary health facilities.